In axiological search of good and evil (book review on Andrii Morozov "Evil: metaphysical and theological dimensions") - M. M. Rohozha, (Ukrainian Cultural Studies, 2022)
From Friedrich Nietzsche, the distinction between philosophers and philosophical laborers is drawn in philosophical circles.
Keywords: book review